1904 Mass. Acts 310-11 - (:unkn) unknown (My University, 1904)
An Act to Authorize the Fire Marshal's Department of the District Police to Make Regulations Relative to Explosives and Inflammable Fluids, ch. 370, §§ 1-2: To regulate the keeping, storage, use, manufacture or sale of gunpowder, dynamite or other explosives and inflammable fluids, shall hereafter be exercised by the fire marshal's department of the district police. § 2. The fire marshal's department of the district police may make regulations for the keeping, storage, use, manufacture or sale of gunpowder,
Keywords: GUNPOWDER - STORAGE